Democracy and the rule of law in classical Athens essays on law, society, and politics - Harris, Edward 1951- (Cambridge University Press, 2006)
This volume brings together essays on Athenian law by Edward M. Harris, who challenges much of the recent scholarship on this topic. Presenting a balanced analysis of the legal system in ancient Athens, Harris stresses the importance of substantive issues and their contribution to our understanding of different types of legal procedures. He combines careful philological analysis with close attention to the political and social contexts of individual statutes. Collectively, the essays in this volume demonstrate the relationship between law and politics, the nature of the economy, the position of women, and the role of the legal system in Athenian society. They also show that the Athenians were more sophisticated in their approach to legal issues than has been assumed in the modern scholarship on this topic